Accelerated treatment with rtPA for pulmonary embolism induced circulatory arrest. Issue 203 (July 2021) - Bakkum, M.J.; Schouten, V.L.; Smulders, Y.M.; Nossent, E.J.; van Agtmael, M.A.; Tuinman, P.R.
Abstract: Patients with circulatory arrest due to pulmonary embolism (PE) should be treated with fibrinolytics. Current guidelines do not specify which regimen to apply, and it has been suggested that the regimen of 100 mg rtPA/2 h should be used, because this is recommended for hemodynamic instable PE in the ESC/ERS Guideline. This two hour regimen, however, is incompatible with key principles of cardiopulmonary resuscitation (CPR), such as employment of interventions that allow fast evaluation of effectiveness, and limitation of the total duration of CPR to avoid poor neurological outcomes. Additionally, the low flow-state during CPR has important consequences for the pharmacokinetic properties of rtPA. Arguably, the volume of distribution is lower, the metabolism reduced and the half life time longer. Therefore, these changes largely discard the rationale to use high dosages of rtPA over a prolonged period of time. More importantly, these changes highlight that the guideline recommendations, based on studies in patients without circulatory arrest, cannot be easily translated to the situation of circulatory arrest. An accelerated regimen of rtPA (0.6 mg/kg/15 min., max 50 mg) is mentioned by the 2019 ESC/ERS Guideline. However, empirical support or a rationale is not provided. Due to the rarity of the situation and ethical difficulties associated with randomizing unconscious patients, a randomized head-to-head comparison between the two regimens is unlikely to ever be performed. With this comprehensive overview of the pharmacokinetics of rtPA and current literature, a strong rationale is provided that the accelerated protocol is the regimen of choice for patients with PE-induced circulatory arrest. Highlights: Hemodynamic unstable pulmonary embolism is treated with 100 mg rtPA in 2 h. This regimen is incompatible with the principles of cardiopulmonary resuscitation. A state of circulatory arrest influences the pharmacokinetic properties of rtPA. A review of the literature shows that accelerated infusion of rtPA is effective. Pulmonary embolism induced arrest should be treated with rtPA 0.6 mg/kg in 15 min.